An exploration of themes that influence the counselor education doctoral student experience. - Protivnak, Jake J; Foss, Louisa L (Counselor Education and Supervision, 2009)
The purpose of the present study was to explore the themes that counselor education doctoral students perceive as influencing their experience. The results of an exploratory qualitative study in which counselor education doctoral students provided their perceptions of what helped or hindered their progress are presented. Themes identified as both positively and negatively influencing their experiences were departmental culture, mentoring, academics, support systems, and personal issues. Recommendations are provided for counselor educators to consider in their work with doctoral students. © 2009 by the American Counseling Association. All rights reserved.
Keywords: dept.csp